PROTOTYPE SISTEM MANAJEMEN KINERJA PEGAWAI NEGERI KANTOR URUSAN AGAMA CIBODAS KOTA TANGERANG - Abdul Hamid Arribathi; Wahyu Hidayat; Rinaldy Qodar Saputra (UNIVERSITAS RAHARJA, 2018)
Office of Religious Affairs (KUA) namely, offices that perform some activities for religion (Islam), especially in marriage and also divorce. In this case, of course, the development of technology in government institutions such as KUA is very important because the amount of information that will be processed into data. Therefore, the researcher will conduct research on one of the KUA offices located in Cibodas sub-district, Tangerang City and find the problem that is, the civil servant performance report system that is still semi-computerized or it can be said still using MS.Excel in the process. Therefore, researchers will develop a civil servant performance report system in KUA cibodas to be more computerized using the Java Desktop programming language used in NetBeans IDE software and assisted with online databases such as MySQL in data storage or files can be stored properly. With the use of this system is expected to facilitate the preparation of civil service performance reports and stored data more structured, efficient, and effective.